Sludge reduction by ozone: Insights and modeling of the dose-response effects. (15th January 2018) - Fall, C.; Silva-Hernández, B.C.; Hooijmans, C.M.; Lopez-Vazquez, C.M.; Esparza-Soto, M.; Lucero-Chávez, M.; van Loosdrecht, M.C.M.
Abstract: Applying ozone to the return flow in an activated sludge (AS) process is a way for reducing the residual solids production. To be able to extend the activated sludge models to the ozone-AS process, adequate prediction of the tri-atoms effects on the particulate COD fractions is needed. In this study, the biomass inactivation, COD mineralization, and solids dissolution were quantified in batch tests and dose-response models were developed as a function of the reacted ozone doses (ROD). Three kinds of model-sludge were used. S1 was a lab-cultivated synthetic sludge with two components (heterotrophs XH and XP ). S2 was a digestate of S1 almost made by the endogenous residues, XP . S3 was from a municipal activated sludge plant. The specific ozone uptake rate (SO3 UR, mgO3 /gCOD.h) was determined as a tool for characterizing the reactivity of the sludges. SO3 UR increased with the XH fraction and decreased with more XP . Biomass inactivation was exponential (e −β.ROD ) as a function of the ROD doses. The percentage of solids reduction was predictable through a linear model (CMiner  + Ysol ROD), with a fixed part due to mineralization (CMiner ) and a variable part from the solubilization process. The parameters of the models, i.e. the inactivation and the dissolution yields (β, 0.008–0.029 (mgO3 /mgCODini ) −1 vs Ysol, 0.5–2.8 mg CODsol /mgO3 ) varied in magnitude, depending on the intensity of the scavenging reactions and potentially the compactness of the flocs for each sludge. Highlights: Dose-response models of O3 sludge reduction were developed for AS modeling. Three model-sludges were used, which had 1, 2 or 3 organic fractions (XP, XH, XI ). Fixed mineralization, linear dissolution and exponential biomass inactivation by O3 . Ozone uptake rate (SO3 UR) as a new tool for sludge reactivity characterization. SO3 UR increases with the fraction XH while scavenging hinders the sludge reduction.